Changing pathological diagnosis from hyperplastic polyp to sessile serrated adenoma: systematic review and meta-analysis. Issue 12 (December 2017) - Niv, Yaron
Abstract : The WHO published a new classification of colonic polyps in 2010, including the group of serrated polyps, which can be divided into hyperplastic polyps (HP), traditional serrated adenomas, and sessile serrated adenomas (SSA) or polyps. To assess the rate of re-diagnosis of HP to SSA and to look for possible predictors for changing the diagnosis. English Medical literature searches were performed for 'reassessment' OR 'reclassification' AND 'hyperplastic polyp' OR 'sessile serrated adenoma' till 31 January 2017. PRISMA guidelines for systematic reviews were followed. Studies that included a precise re-diagnosis of HP into SSA were included. We also looked for predictors of SSA diagnosis such as polyp location and size, patient sex and age, and synchronous advanced adenoma. Altogether, we found 220 eligible studies; 212 were excluded as they did not fulfill the inclusion criteria and we were left with eight studies including 2625 patients. The odds ratio for the number of polyps with changed pathological diagnosis from HP to SSA was 0.112 with 95% confidence interval (CI): 0.099–0.126 ( P <0.0001) or 11.2%. Heterogeneity between studies was significant with Q =199.4, d.f. ( Q )=9, P <0.0001, and I 2 =95.486%. The odds ratio for changing the pathological diagnosis from HP to SSA for polyp proximal location and polyp size more than 5 mm were 4.401, 95% CI: 2.784–6.958, P <0.0001, and 8.336, 95% CI: 4.963–15.571, P <0.0001, respectively. Endoscopists and pathologists should be aware of the SSA diagnosis when finding HPs larger than 5 mm in the right colon. The diagnosis of HP in these cases should be reassessed by experienced gastrointestinal pathologists.